A205 CONGENITAL ABSENCE OF THE PORTAL VEIN: DOES IT REALLY EXIST?. (1st March 2018) - LAVERDURE, N; Lallier, M; Dubois, J; Paganelli, M
Abstract: Background: Congenital portosystemic shunts are rare vascular malformation that can lead to pulmonary hypertension, encephalopathy and liver tumors. They were classified as type I(end-to-side portocaval fistula with no visible portal flow in the liver) and type II(side-to-side portocaval fistula)shunts.Type I shunts are often referred to a congenital absence of the portal vein(CAPV), and are still considered an indication for liver transplantation, whereas surgical or percutaneous closure is usually feasible for type II shunts. Aims: Through a case report and a review of all published patients, we show that what is initially diagnosed as CAPV may conceal a hypoplasic portal vein that can successfully be closed by surgical ligation. Methods: A 2-year-old girl was referred for liver transplantation in the context of recent diagnosis of CAPV. At presentation she was asymptomatic and showed a hypertrophic left liver lobe, without any complications. Her blood tests were normal excepted for moderately elevated serum ammonia levels. MRI confirmed the diagnosis of a type Ib portosystemic shunt(with superior mesenteric and splenic veins joining to form a short portal trunk ending into the inferior vena cava). Percutaneous venogram confirmed the absence of the portal vein. Nevertheless, a second direct catheterization of the shunt with temporary shunt occlusion allowed us to visualize an hypoplasic portal vein arising from the posterior face of the shunt. Pressure was measured at 12mmHg in standard conditions and 36mmHg upon temporary occlusion. We decided for a two-step occlusion. A partial banding was carried out without significant complications(normal liver tests, minimal transient ascites). The shunt was permeable, with a measurable portal flow, at follow-up Doppler ultrasound. 2 months later, moderate elevation of liver enzymes(3xULN) and mild ascites were detected, but resolved spontaneously within a few weeks. The shunt was not detected anymore, and the Doppler study showed a normal portal flow. A percutaneous venogram confirmed the total closure of the shunt and the permeability of the portal vein. The child is asymptomatic at 6-month follow-up. Results: 202 cases of extrahepatic shunts were reported since 1979, of which 134 were described as CAPV. 38 patients(19%) had percutaneous or surgical shunt closure(12 &26, respectively), whereas 25 patients(12%) received a liver transplantation. Among all transplanted patients, only 4% had a preoperative percutaneous venogram with temporary shunt occlusion. Conclusions: Overall, the case reported here exemplifies what emerges from published literature: a precise evaluation of the shunt with percutanous venogram and temporary occlusion is warranted in all patients with suspected CAPV. It allows detecting otherwise invisible hypoplasic portal veins that allow tore establish a physiological hepatic circulation and avoid liver transplantation. Funding Agencies: None